2014
DOI: 10.17711/sm.0185-3325.2014.008
|View full text |Cite
|
Sign up to set email alerts
|

Remisión sintomática y recuperación funcional en pacientes que padecen esquizofrenia

Abstract: SUMMARYA recently proposed definition for remission and recovery in schizophrenia is receiving increased attention by clinicians and researchers. The interest on these issues is based on the recent proposed definition for symptomatic remission, and the development of operational criteria for its assessment, by the Remission in Schizophrenia Working Group (RSWG), in the United States, in 2005. Remission is assessed using eight items of the Positive and Negative Syndrome Scale (PANSS), all of which have to be sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…Psychotic disorders are known to affect functioning (Sumskis, 2013; Valencia et al, 2014; Whiteford et al, 2013). Individuals with psychosis do not only have impaired functioning, they also often have inactive lifestyles due to the impacts of the illness that are further exacerbated by the side effects of antipsychotics (Robson & Gray, 2007; Thongsai et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Psychotic disorders are known to affect functioning (Sumskis, 2013; Valencia et al, 2014; Whiteford et al, 2013). Individuals with psychosis do not only have impaired functioning, they also often have inactive lifestyles due to the impacts of the illness that are further exacerbated by the side effects of antipsychotics (Robson & Gray, 2007; Thongsai et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Invariably, they will need antipsychotic medication to achieve symptomatic remission and psychosocial treatment to improve functioning in the community with the support of their relatives that would need psychoeducation considering recovery as the ultimate goal. Research indicates that symptomatic remission can be achieved by 20-97% of patients and functional recovery by 10-68% 53,[108][109][110][111] Outcome for a person with schizophrenia should be based on medicine-based practices that should include: 1) optimal dose of antipsychotic medication to attain remission of symptoms, 2) Psychosocial and Psychoeducational strategies for patients and relatives to have a real knowledge about the illness that will allow them to cope more efficiently with environmental stresses and learn the corresponding skills for survival in the community, and 3) patients and relatives should have the necessary skills for an assertive home-based management to resolve social problems and needs that would help to prevent crises such as symptom exacerbation. 112 It has been reported that schizophrenia patients satisfied with their life in general had less severe symptoms as well as better functioning than patients who were not satisfied with their lives.…”
Section: Discussionmentioning
confidence: 99%
“…None of the mental disorders have generally accepted criteria for remission. For schizophrenia, two main research groups, in the USA 5 and in Europe, propose different sets of remission criteria . 6 Andreasen's working group defines remission as "a state in which patients have experienced an improvement in core signs and symptoms to the extent that any remaining symptoms are of such low intensity that they no longer interfere significantly with behavior and are below the threshold typically utilized in justifying an initial d i a g n o s i s o f s c h i z o p h r e n i a . "…”
Section: Definitions Of Recovery In Mental Healthmentioning
confidence: 99%